Prevalence of Malaria Among Febrile Patients in Oluyoro Hospital, Ibadan, Oyo State - Adetunji , Rachael; Ajibaye, Sola; Bakare, Omonike Christianah; Adegbehingbe, Kehinde (Sahel Journal of Life Sciences FUDMA, 2025)
Malaria remains a major public health burden in sub-Saharan Africa, with Nigeria accounting for a significant proportion of global cases. This cross-sectional study was conducted at Oluyoro Catholic Hospital, Ibadan, between November 2023 and June 2024, to determine the prevalence of malaria and its distribution across age and gender groups. A total of 350 febrile patients with clinical symptoms of malaria were recruited. Blood samples were collected and analysed using microscopy and rapid diagnostic tests (RDTs). Of the participants, 173 (49.4%) tested positive for malaria. Prevalence was significantly higher among females (53.7%) compared with males (41.3%) (χ² = 4.24; p = 0.039). Children under 15 years carried the greatest burden (63.2%), followed by young adults aged 16–30 years (54.2%). Prevalence declined with age, falling to 25.8% among those aged 31–45 years and 15.9% in individuals above 46 years (p < 0.0001). These trends suggest greater vulnerability among younger individuals due to underdeveloped immunity and increased exposure. Microscopy served as the gold standard for parasite detection. The findings emphasise the importance of targeted malaria control strategies, particularly among children and women. Strengthening diagnostic capacity, expanding access to molecular testing, and implementing routine surveillance are crucial to addressing both Plasmodium falciparum and emerging non-falciparum species. Tailored interventions are needed to reduce malaria morbidity and guide effective treatment approaches.